Impact of arbuscular mycorrhiza on maize P1B-ATPases gene expression and ionome in copper-contaminated soils - Tamara Gómez-Gallego; Ascensión Valderas; Diederik van Tuinen; Nuria Ferrol (Ecotoxicology and Environmental Safety, 2022)
Arbuscular mycorrhizal (AM) fungi, symbionts of most land plants, increase plant fitness in metal contaminated soils. To further understand the mechanisms of metal tolerance in the AM symbiosis, the expression patterns of the maize Heavy Metal ATPase (HMA) family members and the ionomes of non-mycorrhizal and mycorrhizal plants grown under different Cu supplies were examined. Expression of ZmHMA5a and ZmHMA5b, whose encoded proteins were predicted to be localized at the plasma membrane, was up-regulated by Cu in non-mycorrhizal roots and to a lower extent in mycorrhizal roots. Gene expression of the tonoplast ZmHMA3a and ZmHMA4 isoforms was up-regulated by Cu-toxicity in shoots and roots of mycorrhizal plants. AM mitigates the changes induced by Cu toxicity on the maize ionome, specially at the highest Cu soil concentration. Altogether these data suggest that in Cu-contaminated soils, AM increases expression of the HMA genes putatively encoding proteins involved in Cu detoxification and balances mineral nutrient uptake improving the nutritional status of the maize plants.